Dasar-Dasar Etika Politik Franz Magnis Suseno - Wahyu Trisno Aji (Pusat Riset dan Inovasi Nasional, 2024)
This article aims to describe the basics of political ethics from the perspective of Franz Magnis Suseno. The method used is qualitative which aims to analyze and describe the basics of Franz Magnis Suseno's political ethical thought. As a data collection method, it uses library research documentation techniques by including 2 sub points, namely the biography of Franz Magnis Suseno and the basics of his political ethics thinking. The results of the research are that Franz Magnis Suseno's political ethical thinking certainly also has its own unique style of thinking. He is an intellectual who lives in the country of Indonesia which has many diverse cultures. The inspiration for Franz Magnis Suseno's political ethics as far as can be seen is based on 3 things in looking at politics in Indonesia, namely the basis of Catholic teachings which are his beliefs, Javanese ethics which he admires so much and Pancasila as the ideology of the Indonesian nation which he sees as the basis of life for the Indonesian nation. Franz Magnis Suseno sees these three variables in political conditions in Indonesia.